Antifungal prophylaxis in adult patients with acute myeloid leukaemia treated with novel targeted therapies: a systematic review and expert consensus recommendation from the European Hematology Association. Issue 5 (May 2022) - Stemler, Jannik; de Jonge, Nick; Skoetz, Nicole; Sinkó, János; Brüggemann, Roger J; Busca, Alessandro; Ben-Ami, Ronen; Ráčil, Zdeněk; Piechotta, Vanessa; Lewis, Russell; Cornely, Oliver A
Summary: On the basis of improved overall survival, treatment guidelines strongly recommend antifungal prophylaxis during remission induction chemotherapy for patients with acute myeloid leukaemia. Many novel targeted agents are metabolised by cytochrome P450, but potential drug–drug interactions (DDIs) and the resulting risk–benefit ratio have not been assessed in clinical trials, leading to uncertainty in clinical management. Consequently, the European Haematology Association commissioned experts in the field of infectious diseases, haematology, oncology, clinical pharmacology, and methodology to develop up-to-date recommendations on the role of antifungal prophylaxis and management of pharmacokinetic DDIs with triazole antifungals. A systematic literature review was performed according to Cochrane methods, and recommendations were developed by use of the Grading of Recommendations Assessment, Development and Evaluation Evidence to Decision framework. We searched MEDLINE, Embase, and Cochrane Library, including Central Register of Controlled Trials, for randomised controlled trials and systematic reviews published from inception to March 10, 2020. We excluded studies that were not published in English. Evidence for any identified novel agent that is active against acute myeloid leukaemia was reviewed for the following outcomes: incidence of invasive fungal disease, prolongation of hospitalisation, days spent in intensive-care unit, mortality due to invasive fungal disease, quality of life, and potential DDIs. Recommendations and consensus statements were compiled for each targeted drug for patients with acute myeloid leukaemia and each specific setting. Evidence-based recommendations were developed for hypomethylating agents, midostaurin, and the venetoclax–hypomethylating agent combination. For all other agents, consensus statements were given for specific therapeutic settings, specifically for the management of patients with relapsed or refractory acute myeloid leukaemia, monotherapy, and combination with chemotherapy. Antifungal prophylaxis is recommended with moderate strength in most settings, and strongly recommended if the novel acute myeloid leukaemia agent is administered in combination with intensive induction chemotherapy. For ivosidenib, lestaurtinib, quizartinib, and venetoclax, we moderately recommend adjusting the dose of the antileukaemic agent during administration of triazoles. This is the first guidance supporting clinical decision making on antifungal prophylaxis in recipients of novel targeted drugs for acute myeloid leukaemia. Future studies including therapeutic drug monitoring will need to determine the role of dosage adjustment of novel antileukaemic drugs during concomitant administration of CYP3A4-inhibiting antifungals with respect to adverse effects and remission status.